Divergence of human capital in cities in the People's Republic of China: Exploring complementarities and spatial agglomeration of the workforce with various skills - Wenquan Liang; Ming Lu (Asian Development Bank Institute (ADBI), 2016)
In cities, complementarity between a low-skilled and a high-skilled workforce can promote each other to improve labor productivity. In this study, we used earlier census data and 1% population survey data to examine the distribution of the skilled workforce in cities in the People's Republic of China (PRC) along with its changes, and drew the following three conclusions. First, a highly skilled workforce is the engine of urban development, increasing urban wages and population. Second, big cities can promote complementarity between skill sets so that there are greater numbers of high-skilled and low-skilled workers in those cities. This explains why both low-skilled and high-skilled workforces agglomerate in big cities. Last, complementarity between the low-skilled and high-skilled workforce is inhibited in the PRC's cities because of the biased household registration system (HRS) toward the high-skilled workforce, resulting in limited supply of low-skilled labor. This policy is not conducive to enhance labor productivity in big cities and to carry out its leading role of economic growth.
Keywords: J24; J61; R12; 330; People's Republic of China; urbanization; urban development; urban system; city; skill complementarities; skill composition; labor productivity; workforce; economic growth; household registration system; human capital; household income; wages; industrialization; education